THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND DEVELOPMENT OF CHILDREN AGE 0-24 MONTHS AT CIMAHI SELATAN HEALTH CENTER - Yoke Ayukarningsih; Dinar Mutiara; Astrid Febrianti (Journal of Health and Dental Sciences, 2023)
Children with balanced nutritional needs and intake will have good nutritional status, and vice versa; inadequate nutritional intake will affect children's growth and development. This study aims to determine the relationship between nutritional status and the development of children age 0-24 months in the Working Areaf the Cimahi Selatan Health Center in a cross-sectional way. Data on nutritional status were measured using a baby scale for body weight and a length board for body length. At the same time, children's development was assessed using the DDST II form, which consisted of four aspects of development: gross motor, fine motor, language, and personal social. There are 30 subjects in this research selected using consecutive sampling techniques. From the results of the study, it was found that disorders of gross motor development (60.00%), language (100.00%), and personal social (100.00%) were dominant in the 12-24 month age group. In comparison, disorders of fine motor development (33.30%) were found to be equally average in each age group. The results of the analysis showed that there was a significant relationship between aspects of gross motor development (p=0.031), fine motor (p=0.010), language (p=0.045), and personal social (p=0.012) with wasted nutritional status in children 0-24 months in the Cimahi Selatan Health Center Work Area, so it can be concluded that children with wasted nutritional status have a greater risk of experiencing developmental disorders. This result is in line with the theory that inadequate nutritional intake will affect the development process of brain maturity, resulting in a decline in brain function and various delays in child development. DOI : 10.54052/jhds.v3n2.p183.196